Financial Literacy Training to Improve Indonesian Students Self-Competence in the Philippines - Aisyaturrahmi, Aisyaturrahmi; Bhilawa, Loggar; Venusita, Lintang; Satyawan, Made Dudy (PT Inovasi Pratama Internasional, 2025)
Understanding financial literacy is very important for every individual, including students. Students must be able to independently manage their finances effectively and also be responsible for the decisions they have made. Most students also experience financial problems caused by the lack of ability to control personal money (monthly money from parents), not being used to making financial plans, and the habit of hanging out with friends just to gather or go for a walk. So that financial strategies, knowledge and financial literacy are needed in managing student financial planning. Understanding financial planning strategies is a vital thing that every individual student must have in order to lead a prosperous life in the future in facing an independent economy. This type of research is descriptive qualitative using the interview method and supported by training. The results of the study showed that the Indonesian Student Association in the Philippines (PPIF) was satisfied with this training and gained additional understanding of financial literacy so that they could manage their finances effectively.